Evaluation of the Los Angeles County Juvenile Drug Treatment Boot Camp, 1992-1998 - Zhang, Sheldon X. ([Verlag nicht ermittelbar], 2003)
This study was an evaluation of the Los Angeles County Drug Treatment Boot Camp (DTBC). This site was selected because it was one of the earliest boot camps in the nation designed specifically for juvenile offenders. The program enrolled only male offenders between the ages of 16 and 18, who were either documented or alleged drug users with sustained petitions by the juvenile courts for non-violent and non-sex offenses. The main goal of the study was to use a combination of official and self-report measures to assess the effectiveness of the DTBC as a correctional model for juvenile offenders with a focus on their substance-abusing behavior. The study consisted of three independent data collection components: (1) a comparison of official recidivism rates between matched boot camp graduates and non-boot camp graduates over a five-year observation period (Part 1, Official Records Data for Matched Samples), (2) a cross-sectional comparison of self-reports between boot camp and non-boot camp graduates over a 12-month observation period (Part 2, Twelve-Month Self-Report Data), and (3) a pre- and post-test of a boot camp cohort over a six-month observation period (Part 3, Pre- and Post-Test Self-Report Data). Part 1 variables include camp entry and exit dates, sustained petition for camp entry, prior arrests, age at first arrest, most serious charge at first arrest, number of post-camp arrests, most serious charge for post-camp arrests, and number of probation violations post-camp. For Parts 2 and 3, the study utilized the well-established International Self-Report Delinquency questionnaire to assess the youths' post-camp delinquent activities. The instrument contained measures on (1) the types of crimes committed during a specified time frame, (2) the frequency of these delinquent acts, (3) the onset of each admitted offense, (4) the circumstances of the incidents, and (5) a set of sociodemographic variables including attitudes toward school and work, living arrangement, and circle of friends. Demographic variables include age, ethnicity, and country of birth.